Clinical Features of Mycoplasma pneumoniae Infections in the 2010 Epidemic Season: Report of Two Cases with Unusual Presentations - Tomoaki Takei; Miyuki Morozumi; Hirohiko Ozaki; Hisayo Fujita; Kimiko Ubukata; Isshi Kobayashi; Keisuke Kadota; Takako Miyamae; Shumpei Yokota; Satoshi Iwata; Takashi Takahashi (Elsevier, 2013)
Mycoplasma pneumoniae (Mp) is one of the main pathogens causing community-acquired pneumonia, particularly in young individuals. Host immune response appears to play an important role in prolonged symptoms, as well as in the recent increasing prevalence of drug-resistant Mp isolated from patients. Case 1 had a prolonged clinical course caused by drug-resistant Mp and received steroid therapy despite Mp susceptibility to some antimicrobial agents. Serum cytokine profiles revealed elevation of interleukin-6/-10 and interferon-γ in acute phase. Case 2 had mycoplasmal myocarditis without any respiratory symptoms, which resolved spontaneously without the administration of any antimicrobial agent. These observations suggest that host immune response probably contributes to the etiology of Mp-associated complications.